Closing a Window for Massive Photons. (23rd December 2013) - Hojman, Sergio A.; Koch, Benjamin
Abstract : Working with the assumption of nonzero photon mass and a trajectory that is described by the nongeodesic world line of a spinning top we find, by deriving new astrophysical bounds, that this assumption is in contradiction with current experimental results. This yields the conclusion that such photons have to be exactly massless.